ANALYSIS OF THE DETERMINANTS OF LEADERSHIP STYLE - Maman Musa; Darman; Ferilla Ahmad; Windy Rasyid; Ainun Wanda Febrina Anali; Febrianto Hasan (Westscience Press, 2023)
This study tries to explain the determinants of leadership style which consists of personal characteristics and social culture, by observing 51 samples of the Mekar Jaya Village Community, Wonosari District, Boalemo Regency. Data were analyzed using the PLS-SEM technique through SMARTPLS version 3 software. Samples were selected and collected through purposive sampling and distributed via online questionnaire via the Google form. The results show that Personal Characteristics has no significant effect, with a T Statistical value of 1.388 and P Values of 0.166 while Social Cultural Factors has a significant effect, with a T Statistical value of 3.066 and P Values of 0.002 on Leadership Style.